Profil Kecerdasan Adversitas Siswa Berlatar Belakang Budaya Minangkabau - Puji Gusri Handayani; Hafiz Hidayat; Verlanda Yuca; Rahmi Dwi Febriani; Frischa Meivilona Yendi (Universitas Negeri Padang, 2023)
Adversity quotient affects the ability in learning and also student learning achievement, in addition, the adversity quotient affects how a person overcomes the ability to problems. Because of this problem, it takes a high adversity quotient to be able to survive in all conditions. The purpose of this study was to describe the adversity quotient of MAN 1 Padang students and test the difference in the adversity quotient of male and female students. This study uses a comparative quantitative approach. The sample in the study was 130 students, of which 55 were male and 65 were female students. With sampling techniques that are simple random sampling. The measurement used is